Karakteristik Religius Kultur Kampus Dalam Keseharian Mahasiswa Universitas Pendidikan Indonesia - Nurjannah, Dini; Sari, Sofi Wulan; Oktaviani, Tanti; Fakhruddin, Agus (Institut Agama Islam Negeri Kediri, 2023)
Abstract: Various religious activities are a mandatory aspect for all Muslim students at Universitas Pendidikan Indonesia (UPI) to embody the